1987
DOI: 10.1007/bf00292540
|View full text |Cite
|
Sign up to set email alerts
|

Haemolysis affects insulin but not C-peptide immunoassay

Abstract: Venous blood was taken at the end of a glucose infusion test in 19 individuals and divided into four aliquots, 3 of which were variably haemolysed by repeated passage through a 23-gauge needle to simulate traumatic venepuncture. Plasma insulin (measured by both a charcoal separation and a double-antibody method), C-peptide, and haemoglobin were measured in each aliquot, and haemolysis was also assessed visibly. A significant loss of immuno-assayable plasma insulin was found in samples with only a trace of visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 6 publications
0
44
1
Order By: Relevance
“…We chose to measure C-peptide rather than insulin because the C-peptide concentration is not altered by hemolysis, whereas insulin degradation is increased by even small amounts of hemolysis. 32 TNDM patients with 6q24 abnormalities present with hyperglycemia during the few weeks of post-natal life due to a failure of insulin production. 15,33,34 In our study population, the ZAC1 DMR MI was not significantly associated with the cord blood concentration of C-peptide.…”
Section: Discussionmentioning
confidence: 99%
“…We chose to measure C-peptide rather than insulin because the C-peptide concentration is not altered by hemolysis, whereas insulin degradation is increased by even small amounts of hemolysis. 32 TNDM patients with 6q24 abnormalities present with hyperglycemia during the few weeks of post-natal life due to a failure of insulin production. 15,33,34 In our study population, the ZAC1 DMR MI was not significantly associated with the cord blood concentration of C-peptide.…”
Section: Discussionmentioning
confidence: 99%
“…Cord serum levels of C-peptide are used as an index of fetal beta-cell function, rather than insulin levels, because degradation of insulin is increased in the presence of slight hemolysis. 8 In a previous study Kuhl et al 9 reported that IDMs who became hypoglycemic at 2 hours of life had significantly higher levels of glucose and immunoreactive insulin in cord blood than IDMs who remained normoglycemic. Metzer B E et al 10 also found that frequency of neonatal hypoglycemia was higher with higher cord C-peptide levels and newborns with hypoglycemia tended to have a higher frequency of cord C-peptide levels of more than 90 th percentile.…”
Section: Introductionmentioning
confidence: 96%
“…Regarding the results observed with the IRMA insulin-specific assay, in the 52 samples taken from the 15 patients at the time of symptomatic hypoglycaemia of 0.45 g/l or less, insulin-IRMA levels were below 6 mIU/l in all the serum samples in six patients (patients 2, 3, 4, 5, 13, 14), and in some of the serum samples in three patients (1, 9, 15); insulin-IRMA levels even reached values below 3 mIU/l in five patients (2,3,4,13,14). Insulin-IRMA exceeded the 6 mIU/l threshold in all the serum samples in only six patients (6,7,8,10,11,12). Table 2 Results of blood glucose, insulin-IRMA, insulin-RIA and C-peptide levels observed before surgery at the time of symptomatic hypoglycaemia of 0.45 g/l or less in the 15 patients.…”
Section: Resultsmentioning
confidence: 92%
“…Blood glucose, serum insulin and C-peptide levels were measured during spontaneous symptomatic hypoglycaemia in 6 patients (patients 1, 2, 6, 7, 10, 11) and during a fast test in 13 patients (patients 2,3,4,5,6,7,8,9,11,12,13,14,15). The fast test was discontinued at the time when symptomatic hypoglycaemia occurred, with blood glucose below 0.45 g/l.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation